Antibiotic prescribing for the older adult: beliefs and practices in primary care - Hayward, G; Moore, A; McKelvie, S; Lasserson, D; Croxson, C (Oxford University Press, 2018)
Background: Older adults suffer high morbidity and mortality following serious infections, and hospital admissions with these conditions are increasingly common. Antibiotic prescribing in the older adult population, especially in long-term care facilities, has been argued to be inappropriately high. In order to develop the evidence base and provide support to GPs in achieving antimicrobial stewardship in older adults it is important to understand their attitudes and beliefs toward antibiotic prescribing in this population. Objectives: To understand the attitudes and beliefs held by GPs regarding antibiotic prescribing in older adults. Methods: Semi-structured qualitative interviews were conducted with 28 GPs working in the UK. Data analysis followed a modified framework approach. Results: GPs described antibiotic prescribing in older adults as differing from prescribing in other age groups in a number of ways, including prescribing broad-spectrum, longer and earlier antibiotics in this population. There were also rationales for situations where antibiotics were prescribed despite there being no clear diagnosis of infection. Trials of antibiotics were used both as diagnostic aids and in an attempt to avoid admission. The risks of antibiotics were understood, but in some cases restrictions on antibiotic use were thought to hamper optimal management of infection in this age group. Conclusions: Diagnosing serious infections in older adults is challenging and antibiotic prescribing practices reflect this challenge, but also reflect an absence of clear guidance or evidence. Research that can fill the gaps in the evidence base is required in order to support GPs with their critical antimicrobial stewardship role in this population.